Emerging Functions of RANKL in Lymphoid Tissues - Mueller, Christopher G.; Hess, Estelle (Frontiers in Immunology, 2012)
The tumor necrosis factor superfamily (TNFSF) members play pivotal roles in embryonic development of lymphoid tissue and in their homeostasis. RANKL (Receptor activator of NF-kappaB ligand, also called TRANCE, TNFSF11) is recognized as an important player in bone homeostasis and in lymphoid tissue formation. In its absence bone mass control is deregulated and lymph nodes fail to develop. While its function in bone is well described, there is still little functional insight into the action of RANKL in lymphoid tissue development and homeostasis. Here we provide an overview of the known functions of RANKL, its signaling receptor RANK and its decoy receptor OPG from the perspective of lymphoid tissue development and immune activation in the mouse. Expressed by the hematopoietic lymphoid tissue inducing (LTi) cells and the mesenchymal lymphoid tissue organizer (LTo) cells, RANKL was shown to stimulate lymphotoxin (LT) expression and to be implicated in LTi cell accumulation. Our recent finding that RANKL also triggers proliferation of adult lymph node stroma suggests that RANKL may furthermore directly activate LTo cells. Beyond bone, the RANKL-RANK-OPG triad plays important roles in immunobiology that are waiting to be unraveled.